2015
DOI: 10.1111/wre.12172
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Avena fatua populations with resistance to multiple herbicides

Abstract: Avena fatua (wild oat) populations with resistance (R) to one or more herbicides have been described in numerous cropping systems worldwide. We previously reported that the R3 and R4 wild oat populations from Montana, USA, were resistant to four herbicides representing three different modes of action: tralkoxydim [acetyl-CoA carboxylase (ACCase] inhibitor), imazamethabenz and flucarbazone [acetolactate synthase (ALS) inhibitors] and difenzoquat (growth inhibitor). We now quantify resistance levels of these pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 36 publications
1
49
0
Order By: Relevance
“…Field‐collected seeds (about 90% of which were resistant to 60 g a.i. ha −1 pinoxaden, data not shown) were subjected to two generations of recurrent group selection (50 plants each generation) by spraying with the same dose of pinoxaden, after which 100% of plants were confirmed to be homozygous resistant to pinoxaden via dose response experiments . From each generation of 50 plants, all seeds were harvested and a random selection of 50 seeds was used to initiate five additional generations without herbicide selection to homogenize the genetic background.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Field‐collected seeds (about 90% of which were resistant to 60 g a.i. ha −1 pinoxaden, data not shown) were subjected to two generations of recurrent group selection (50 plants each generation) by spraying with the same dose of pinoxaden, after which 100% of plants were confirmed to be homozygous resistant to pinoxaden via dose response experiments . From each generation of 50 plants, all seeds were harvested and a random selection of 50 seeds was used to initiate five additional generations without herbicide selection to homogenize the genetic background.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…From each generation of 50 plants, all seeds were harvested and a random selection of 50 seeds was used to initiate five additional generations without herbicide selection to homogenize the genetic background. The HS1 population was derived from seeds collected from untreated border plants in an adjacent field, grown for seven generations as described for MHR4 except without herbicide selection, and was subsequently confirmed to be 100% susceptible to the herbicides used in these studies . A second susceptible population HS2 used for crossing studies (see below) is the highly inbred nondormant SH430 line used in seed dormancy research .…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, it is also a malignant weed that harms wheat, oilseed rape, and other crops in China and has developed serious resistance to herbicides all over the world (Cavan et al 2001). In recent years, qPCR has been widely used to quantify gene expression levels in diverse studies of A. fatua, such as studies of herbicide resistance and ecological adaption (Li et al 2009;Cruzhipolito et al 2011;Keith et al 2015). Some studies have shown that at least two or three reference genes should be used to achieve accurate normalisation (Thellin et al 1999;Vandesompele et al 2002).…”
mentioning
confidence: 99%